A systematic assessment of current genome-scale metabolic reconstruction tools - Mendoza, Sebastián N.; Olivier, Brett G.; Molenaar, Douwe; Teusink, Bas (Genome biology, 2019)
Several genome-scale metabolic reconstruction software platforms have been developed and are being continuously updated. These tools have been widely applied to reconstruct metabolic models for hundreds of microorganisms ranging from important human pathogens to species of industrial relevance. However, these platforms, as yet, have not been systematically evaluated with respect to software quality, best potential uses and intrinsic capacity to generate high-quality, genome-scale metabolic models. It is therefore unclear for potential users which tool best fits the purpose of their research.